The Probability of Caries in Preschool Children when Detecting STR. Mutant - Turayev Alimjan Baxriddinovich (Scientific Trends, 2024)
This paper presents the first results of a study on the diagnosis of early dental caries in Voronezh. The study included 30 preschool children who were examined in the morning and evening for the presence of Str. caries in saliva. The use of a modern reagent made it possible to quickly and reliably determine the quantitative content of cariesogenic Streptococcus spp. This method can be used to identify risk factors for the development of caries at an early stage and for the prevention of caries in young children.
Keywords: Dental caries, Str. mutans, childhood, prevention.